2023
DOI: 10.1186/s12951-023-01800-x
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity ultrasound-mediated drug-loaded nanoparticles intravaginal drug delivery: an effective synergistic therapy scheme for treatment of vulvovaginal candidiasis

Abstract: Purpose Vulvovaginal candidiasis (VVC) is a mucosal infection of the female lower genital tract for which treatment using conventional antifungal drugs shows limited effectiveness. Herein, amphotericin B-loaded poly(lactic-co-glycolic acid)-polyethylene glycol (PLGA-PEG) nanoparticles (AmB-NPs) were fabricated and combined with low intensity ultrasound (US) to mediate AmB-NPs intravaginal drug delivery to achieve productive synergistic antifungal activity in a rabbit model of VVC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Further analysis at the phylum level revealed that US treatment markedly increased the relative abundance of Firmicutes , reshaping the healthy vaginal microbiome ( Figure 12H ). On the basis of effective antifungal results obtained in the previous study of US-mediated AmB-NPs therapy for VVC infection, 20 these part results further confirmed that US-mediated AmB-NPs treatment exhibits excellent therapeutic efficacy against C. albicans vaginal biofilms in vivo, promotes the recovery of damaged mucosal epithelial ultrastructure, and contributes to the reshaping of a healthier vaginal microbiome.
Figure 12 Antifungal effects of US-mediated AmB-NPs on vaginal C. albicans biofilms in vivo.
…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Further analysis at the phylum level revealed that US treatment markedly increased the relative abundance of Firmicutes , reshaping the healthy vaginal microbiome ( Figure 12H ). On the basis of effective antifungal results obtained in the previous study of US-mediated AmB-NPs therapy for VVC infection, 20 these part results further confirmed that US-mediated AmB-NPs treatment exhibits excellent therapeutic efficacy against C. albicans vaginal biofilms in vivo, promotes the recovery of damaged mucosal epithelial ultrastructure, and contributes to the reshaping of a healthier vaginal microbiome.
Figure 12 Antifungal effects of US-mediated AmB-NPs on vaginal C. albicans biofilms in vivo.
…”
Section: Resultssupporting
confidence: 70%
“… 19 In previous studies, we have demonstrated that ultrasound-mediated AmB-loaded nanoparticles can improve the efficiency of intravaginal drug delivery and play a highly effective antifungal role in in vitro plankton Candida and in vivo VVC infection. 20 However, how ultrasound-mediated nanoparticles penetrate the double barrier of mucus and biofilm, as well as the clearance effect of sonodynamic effects on the Candida biofilm associated with the epithelium under the mucus barrier and the local antifungal immunomodulation effect on cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these approaches have leveraged on the growing applications of nanotechnologies to enhance drug delivery. One such effort was the development of low-intensity ultrasound-mediated drug-loaded nanoparticles to facilitate the intravaginal delivery of amphotericin B against VVC [17]. Although this approach led to some improvement in the antifungal activity of the drug candidate (amphotericin B), the formulation technique (and required materials) can be characterized as quite sophisticated and may not be feasible for bulking-up and commercial development, especially in developing and underdeveloped regions of the world.…”
Section: Introductionmentioning
confidence: 99%